(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
India’s religious traditions have evolved through sustained interaction across cultures, languages, and spiritual systems. Syncretism defined as the blending or cross-fertilisation of ideas, practices, and symbols has been a hallmark of the subcontinent’s intellectual history. This paper examines syncretism within major Indian religions and situates Sikhism within this broader landscape. While Sikhism appeared amid rich inter-religious dialogue, it simultaneously articulated a distinct theological vision. Through an overview of Vedic-Shramanic exchanges, Bhakti-Sufi interactions, and the pluralistic milieu of medieval Punjab, the paper evaluates scholarly debates on whether Sikhism is a syncretic tradition or an original revelation that engaged with its context in transformative ways.